Analysis of ethylene oxide in ice creams manufactured with contaminated carob bean gum (E410). Issue 12 (2nd December 2021) - Bessaire, Thomas; Stroheker, Thomas; Eriksen, Bjorn; Mujahid, Claudia; Hammel, Yves-Alexis; Varela, Jesus; Delatour, Thierry; Panchaud, Alexandre; Mottier, Pascal; Stadler, Richard H.
ABSTRACT: Residues of ethylene oxide (EO), a banned fumigant in the EU, were found at amounts above the maximum residue limit (MRL) in carob (locust) bean gum (additive E410). The pesticide entered the food chain via stabiliser blends that are used as minor ingredients in the manufacture of ice cream. Consequently, all products that contained the non-compliant ingredient were withdrawn or recalled in several countries across the EU, in most cases irrespective of whether the pesticide residue was detectable or not in the final product. This is the first report of a reliable method to determine EO and its metabolite/marker compound 2-chloroethanol (2-CE), either together or independently in ice cream, with a limit of quantification at 0.01 mg EO/kg and recovery in the range of 87–104% across the levels investigated (0.01, 0.02 and 0.06 mg EO/kg). The method applies QuEChERS extraction and isotope dilution gas chromatography coupled with tandem mass spectrometry (GC-MS/MS). High resolution mass spectrometry (HRMS) confirmed the specificity of low mass ions. Data on the stability of EO and 2-CE under thermal conditions revealed that 2-CE is relatively stable in an ice cream matrix (ca. 80% recovery of spiked material). Importantly, this study also demonstrates that not EO, but 2-CE is the predominant analyte detected in the contaminated samples, which is new information of significance in terms of the overall risk assessment of EO in foodstuffs.